Investigation of probiotics in multiple sclerosis. (January 2018) - Tankou, Stephanie K; Regev, Keren; Healy, Brian C; Cox, Laura M; Tjon, Emily; Kivisakk, Pia; Vanande, Isabelle P; Cook, Sandra; Gandhi, Roopali; Glanz, Bonnie; Stankiewicz, James; Weiner, Howard L
None of the disease-modifying therapies (DMTs) currently being used for the management of multiple sclerosis (MS) are 100% effective. In addition, side effects associated with the use of these DMTs have limited the practice of combination therapy. Hence, there is a need for safe immunomodulatory agents to fine-tune the management of MS. The gut microbiome plays an important role in autoimmunity, and several studies have reported alterations in the gut microbiome of MS patients. Studies in animal model of MS have identified members of the gut commensal microflora that exacerbate or ameliorate neuroinflammation. Probiotics represent an oral, non-toxic immunomodulatory agent that could be used in combination with current MS therapy. We designed a pilot study to investigate the effect of VSL3 on the gut microbiome and peripheral immune system function in healthy controls and MS patients. VSL3 administration was associated with increased abundance of many taxa with enriched taxa predominated by Lactobacillus, Streptococcus, and Bifidobacterium species. At the immune level, VSL3 administration induced an anti-inflammatory peripheral immune response characterized by decreased frequency of intermediate monocytes (CD14 high CD16 low ), decreased mean fluorescence intensity (MFI) of CD80 on classical monocytes as well as decreased human leukocyte antigen–antigen D related (HLA-DR) MFI on dendritic cells.